PARTISIPASI PENGANGGARAN, KEPUASAN KERJA, KOMITMEN ORGANISASI, DAN KINERJA APARAT PEMERINTAH BADAN PERTANAHAN NASIONAL PROVINSI BENGKULU - Ridha, Ridha; Fadli, Fadli; Halimatusyadiah, Halimatusyadiah (JURNAL FAIRNESS, 2020)
This research was aimed to analyze the participation in budgeting, job satisfaction, and organizational commitment to performance. Participation in budgeting is a common approach that can improve performance because in participation there is the delegation of procedures and involvement in decision making. Job satisfaction depends on what the individual feels towards his job and requires someone to interact with companions and commanders, follow the rules, and achieve performance standards. Organizational commitment is an emotional attachment, individual involvement in the organization, and the preference to stay on the organization. The results of this study showed that participation in budgeting variables does not significantly affect on managerial performance, job satisfaction variables significantly influence managerial performance and the organizational commitment variables have a significant effect on managerial performance.